Algicide capacity of Paucibacter aquatile DH15 on Microcystis aeruginosa by attachment and non-attachment effects. (1st June 2022) - Le, Ve Van; Ko, So-Ra; Kang, Mingyeong; Lee, Sang-Ah; Oh, Hee-Mock; Ahn, Chi-Yong
Abstract: The excessive proliferation of Microcystis aeruginosa can lead to ecological damage, economic losses, and threaten animal and human health. For controlling Microcystis blooms, microorganism-based methods have attracted much attention from researchers because of their eco-friendliness and species-specificity. Herein, we first found that a Paucibacter strain exhibits algicidal activity against M. aeruginosa and microcystin degradation capability. The algicidal activity of DH15 (2.1 × 10 4 CFU/ml) against M. aeruginosa (2 × 10 6 cells/ml) was 94.9% within 36 h of exposure. DH15 also degraded microcystin (1.6 mg/L) up to 62.5% after 72 h. We demonstrated that the algicidal activity of DH15 against M. aeruginosa can be mediated by physical attachment and indirect attack: (1) Both washed cells and cell-free supernatant could kill M. aeruginosa efficiently; (2) Treatment with DH15 cell-free supernatants caused oxidative stress, altered the fatty acid profile, and damaged photosynthetic system, carbohydrate, and protein metabolism in M. aeruginosa . The combination of direct and indirect attacks supported that strain DH15 exerts high algicidal activity against M. aeruginosa . The expression of most key genes responsible for photosynthesis, antioxidant activity, microcystin synthesis, and other metabolic pathways in M. aeruginosa was downregulated. Strain DH15, with its microcystin degradation capacity, can overcome the trade-off between controlling Microcystis blooms and increasing microcystin concentration. Our findings suggest that strain DH15 possesses great potential to control outbreaks of Microcystis blooms. Graphical abstract: Image 1 Highlights: The first recorded Paucibacter strain with algicidal activity against Microcystis. Strain DH15 kills Microcystis efficiently by both direct and indirect attacks. Strain DH15 induces oxidative stress and destroys several biological processes of Microcystis. Strain DH15 is capable of degrading microcystin.